Clinical and Echographic Features of Morning Glory Disc Anomaly in Children: A Retrospective Study of 249 Chinese Patients - Zou, Yihua; She, Kaiqin; Hu, Yiqian; Ren, Jianing; Fei, Ping; Xu, Yu; Peng, Jie; Zhao, Peiquan (Frontiers in Medicine, 2022)
PURPOSE To report the clinical and echographic features, the prevalence of retinal detachment (RD), and associated visual acuity in a cohort of pediatric patients with of morning glory disc anomaly (MGDA). METHODS This was a retrospective review of 249 pediatric patients with MGDA (271 eyes) seen at the Dept. of Ophthalmology, Xinhua Hospital. Their medical records were reviewed for demographic data, ocular and systemic findings. The maximal depth and width of the cavity were measured using standardized echographic images. The ratios of cavitary depth to axial length, cavitary depth to maximal cavitary width and the product of cavitary depth and width were calculated and used to indicated the relative size of the excavation. The clinical and echographic findings were correlated with visual acuity and the occurrence of RD of the patient. RESULTS The relative size of the excavation and the presence of RD were positively associated with increased risk of poor vision (p<0.05). The presence of persistent fetal vasculature was not associated with the risk of RD and poor vision. A ratio of cavitary depth to axial length greater than 0.25 conferred an increased risk of RD (OR, 2.101; 95% CI 1.469-3.003). CONCLUSIONS Clinical and echographic features of MGDA may be used in predicting the risk of RD. Measuring the relative size of excavation via echography may guide the follow-ups and assist in the early diagnosis of RD.